Novel Hydrogel Material with Tailored Internal Architecture Modified by "Bio" Amphiphilic Components-Design and Analysis by a Physico-Chemical Approach - Heger, Richard; Kadlec, Martin; Trudicova, Monika; Zinkovska, Natalia; Hajzler, Jan; Pekar, Miloslav; Smilek, Jiri (Gels (Basel, Switzerland), 2022)
Nowadays, hydrogels are found in many applications ranging from the industrial to the biological (e.g., tissue engineering, drug delivery systems, cosmetics, water treatment, and many more). According to the specific needs of individual applications, it is necessary to be able to modify the properties of hydrogel materials, particularly the transport and mechanical properties related to their structure, which are crucial for the potential use of the hydrogels in modern material engineering. Therefore, the possibility of preparing hydrogel materials with tunable properties is a very real topic and is still being researched. A simple way to modify these properties is to alter the internal structure by adding another component. The addition of natural substances is convenient due to their biocompatibility and the possibility of biodegradation. Therefore, this work focused on hydrogels modified by a substance that is naturally found in the tissues of our body, namely lecithin. Hydrogels were prepared by different types of crosslinking (physical, ionic, and chemical). Their mechanical properties were monitored and these investigations were supplemented by drying and rehydration measurements, and supported by the morphological characterization of xerogels. With the addition of natural lecithin, it is possible to modify crucial properties of hydrogels such as porosity and mechanical properties, which will play a role in the final applications.
Keywords: extracellular matrix; lecithin; hydrogel; scanning electron microscopy; rheology; drying and swelling; mesh size